A Study of the Biological Activity of Bee Venom and its Fractions With Regard to Cosmetic Science and Immunology - Tusiimire, Jonans (University of Strathclyde Science, 2016)
Apis mellifera venom has been used since antiquity to treat various ailments but sci-entific evidence to justify its therapeutic claims is incomplete. The venom has recent-ly entered cosmetic usage as a mimetic ingredient to alleviate signs of facial aging. This study investigated the potential of bee venom (BV) as a source of cosmetic and immunomodulatory agents for use in skin anti-ageing applications and as a vaccine adjuvant, respectively. BV fractions were obtained by reversed phase preparative chromatography and characterised by LC-MS and NMR techniques. The fractions were assayed for antimicrobial and cytotoxic activities against a range of microbes (Mycobacterium marinum, Norcardia farcinia and Trypanosoma brucei brucei) and human cell lines [NCTC2544 (normal keratinocytes), PNT2A (normal epithelial cells), and HS27 (normal fibroblasts)] respectively. Immunomodulatory effects were investigated in PMA-differentiated U937 cells with and without LPS co-stimulation. The aqueous stability of the venom and its susceptibility to protease action were as-sessed by LC-MS assays. An LC-MS method was also developed and validated for the assay of BV in commercial creams using the melittin signal as an indicator of BV content. Of the 4 BV fractions (F-1 to F-4), the largest, containing melittin, showed the most activity against N. farcinia (25-50μg/mL) and T. b. brucei (0.78-1.56μg/mL), but was not very active against M. marinum (>100μg/mL). The melittin fraction (96% pure) was the most cytotoxic against keratinocytes, fibroblasts and epi-thelial cells, with IC50 ≥ 2.5-4.0μg/mL. All fractions significantly enhanced IL-1β release, while only F-4, a lipophilic fraction, enhanced TNF-α release. F-4, which was revealed through NMR elucidation to contain (Z)-9-eicosen-1-ol, produced sig-nificant inhibition of IL-6 release. Melittin in aqueous solutions of BV, but not of the melittin fraction alone, underwent a temperature-dependent spontaneous degradation within the 21Lys-22Arg-23Lys-24Arg sequence due to a serine carboxypeptidase-like activity attributed to the BV allergen, Api m9. Taken together, these results suggest that a formulation matching the 3.2–37.2ppm content of melittin assayed in commer-cial creams would be safe for skin application based on IC50 values in human cells. The immunomodulatory effects observed in U937 cells highlight the potential of BV as a possible source of vaccine adjuvants.
Keywords: Biological Activity; Bee Venom; Cosmetic usage; Skin anti-ageing